Differences between Managing Traditional Projects and Innovation Projects - Frederico ARAUJO; Anabela TERESO; Kathryn CORMICAN (Communications of International Proceedings, 2021)
While project management and innovation management are separate and distinct disciplines, both areas have connections that merit exploration. The scope of this study is to clarify the differences between managing traditional projects and managing innovation projects and finding connections in both research areas using a systematic literature review. This study found that traditional projects and innovation projects differ in many aspects and must be managed differently, according to their specifications and characteristics. Traditional projects have characteristics comprising strong planning and control and usually follow linear and progressive phases. On the other hand, innovation projects require flexibility, the ability to think freely and adapt to change, as the objective is to improve some product or process, adding value, or creating something new. For innovation management there is no best practice. The methodology applied will depend on the type of project, the level of innovation, the degree of knowledge involved and the company environment.
Keywords: Innovation Management; Innovation Projects; Project Management; Traditional Projects.